The cruelty of hope: Emotional cultures of precarity in neoliberal Cairo. (August 2019) - Pettit, Harry
Contemporary labour markets around the world are pushing more and more people into cycles of un/underemployment, or what has been labelled precarious life. This paper adds to work on precarity's lived experience, first, by highlighting the production of a precarious lower-middle class group in the global South – young educated underemployed men in Egypt. It then uses five months of ethnography to trace the emotional endurance of precarity with rural migrants in Cairo who work in call centres. Departing from recent emphasis on political forms of resistance or creative survival arising from precarious lives, the paper extends both culturally specific accounts of hope and Lauren Berlant's notion of cruel optimism to a post-revolutionary Egyptian context, showing how, despite lingering anger regarding structural explanations for precarity, my interlocutors repeatedly coped with a sense of suspension through engaging in forms of consumption which distracted their minds, and hanging on to a globalised meritocratic terrain through self-help, Hollywood movies, and religious narratives, which offered 'cruel hope', promising success to those who work hard.